Bystander Student's Perception about Bullying Behavior - Dwina Ivoni Lauren; Daharnis Daharnis; Afdal Afdal (Universitas Negeri Padang, 2019)
Bullying is the behavior of a person or group that has the power to oppress a person or group that he considers weak from him. Bullying has the form of direct physical contact, direct verbal, non-verbal direct, non-verbal indirect and sexual harassment. This study aims to describe the perceptions of student's bystander about bullying behavior. The study population was 233 students at 7 Public Middle School in Kerinci and a sample of 65 students were selected using the Purposive Sampling technique. The instrument used was a questionnaire in the form of a Likert scale, data were analyzed using simple statistical techniques. The research findings revealed that bystander student's perceptions abaout bullying behavior were generally good, meaning that bystander student's did not support the behavior carried out by bullying offenders. Although there are still student's who perceive not to be good.